Adaptive Biomedical Innovation: Evolving Our Global System to Sustainably and Safely Bring New Medicines to Patients in Need. Issue 6 (22nd October 2016) - Hirsch, G; Trusheim, M; Cobbs, E; Bala, M; Garner, S; Hartman, D; Isaacs, K; Lumpkin, M; Lim, R; Oye, K; Pezalla, E; Saltonstall, P; et al.
Abstract : The current system of biomedical innovation is unable to keep pace with scientific advancements. We propose to address this gap by reengineering innovation processes to accelerate reliable delivery of products that address unmet medical needs. Adaptive biomedical innovation (ABI) provides an integrative, strategic approach for process innovation. Although the term "ABI" is new, it encompasses fragmented "tools" that have been developed across the global pharmaceutical industry, and could accelerate the evolution of the system through more coordinated application. ABI involves bringing stakeholders together to set shared objectives, foster trust, structure decision‐making, and manage expectations through rapid‐cycle feedback loops that maximize product knowledge and reduce uncertainty in a continuous, adaptive, and sustainable learning healthcare system. Adaptive decision‐making, a core element of ABI, provides a framework for structuring decision‐making designed to manage two types of uncertainty – the maturity of scientific and clinical knowledge, and the behaviors of other critical stakeholders.